From Digital Collectibles to Zakatable Income: A Sharia and Regulatory Analysis of NFT Creator Earnings in Indonesia - Muhammad Abdul Aziz; Syafiq Mahmadah Hanafi; Muhammad Luqman Ammar; Luthfi Muhyiddin (Hikmatuna : Journal for Integrative Islamic Studies, 2026)
This study aims to analyze the zakat status of non-fungible token (NFT) creator earnings in Indonesia and to formulate an appropriate payment mechanism from the perspective of Islamic finance and national regulation. The study employs a qualitative descriptive approach based on library research and semi-structured interviews, involving key informants from the National Zakat Agency (BAZNAS) and the Ministry of Religious Affairs of the Republic of Indonesia, supported by zakat jurisprudence, regulatory documents, and relevant NFT literature. The findings show that the object of zakat does not lie in the NFT as a digital token itself, but in the income realized from sales and royalties. Such income is more appropriately classified as income or professional zakat, with a nisab equivalent to 85 grams of gold and a 2.5% rate after fulfilling the requirements of haul and lawful ownership. The study also finds that, in the Indonesian context, zakat on NFT creator earnings cannot yet be paid in cryptocurrency due to both regulatory and Sharia considerations; therefore, such earnings must first be converted into lawful local currency. This study recommends the development of clearer zakat guidelines for digital assets, broader empirical research on NFT creators, and a more adaptive regulatory framework in response to the expansion of the digital economy.